Implementasi Asesmen Formatif pada Pembelajaran Menulis Karya Sastra: Kajian Evaluatif di Tingkat Sekolah Menengah Atas - Eny Junyanti; Ika Septiana (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This study examines the implementation of formative assessment in creative writing instruction at the senior high school level through a comprehensive evaluative approach. The research addresses the critical need for effective assessment practices in literature education, particularly in developing students' creative writing competencies. Using a mixed-method design, data were collected from 156 students and 12 teachers across six senior high schools through classroom observations, semi-structured interviews, document analysis, and student performance assessments over one academic semester. The findings reveal that systematic implementation of formative assessment significantly enhanced students' writing proficiency, with a 68% improvement in creative expression and a 72% increase in technical writing skills. The study identified key success factors including continuous feedback mechanisms, digital assessment tools integration, and collaborative learning environments. However, challenges such as time constraints and technological adaptation were noted. This research contributes to the development of evidence-based assessment practices in literature education and provides practical recommendations for enhancing creative writing instruction at the secondary education level.